Characterization of the understory in dense pine and fir forests of the Nevado de Toluca - Mejía Canales, Ana; Franco-Maass, Sergio; Endara Agramont, Angel Rolando; Ávila Akerberg, Víctor (Instituto de Ecología, A.C., 2018)
The greatest floristic diversity of the temperate forests is found in the herbaceous and shrubby component of the undergrowth, in which the flora acquires great ecological and functional importance. Essential processes of the nutrient cycle and the successional trajectory, depend directly on the vegetation of the understory. This study determined the composition and structure of the herbaceous and shrub species in dense forests of Pinus hartwegii (Lindl) and Abies religiosa (Kunth Schltdl and et Cham.) of the Nevado de Toluca and quantified the abundance of tree regeneration in 10 quadrants continuous of 10 m × 10 m. In the species smaller than 50 cm the coverage and abundance was estimated based on the Braun-Blanquet scale and, in the species greater than 50 cm, the relative value in coverage, frequency and density were obtained, besides their value of importance. According to our results, the understory of the forests of Abies religiosa is greater in diversity and is composed of 33 species, 25 genera and 14 families, where Asteraceae is the dominant family. The understory of Pinus hartwegii is composed by 18 species, 16 genera and 10 families, with dominance in coverage and abundance of the family Poaceae. In both, plant communities’ regeneration is greater in seedlings and less in small and large saplings.